2005
DOI: 10.1289/ehp.8384
|View full text |Cite
|
Sign up to set email alerts
|

Case–Control Study of an Acute Aflatoxicosis Outbreak, Kenya, 2004

Abstract: Objectives: During January–June 2004, an aflatoxicosis outbreak in eastern Kenya resulted in 317 cases and 125 deaths. We conducted a case–control study to identify risk factors for contamination of implicated maize and, for the first time, quantitated biomarkers associated with acute aflatoxicosis.Design: We administered questionnaires regarding maize storage and consumption and obtained maize and blood samples from participants.Participants: We recruited 40 case-patients with aflatoxicosis and 80 randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
279
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(307 citation statements)
references
References 18 publications
7
279
2
4
Order By: Relevance
“…Highly significant associations between AFB-Lys adduct level and dietary AFB 1 exposure have been found in human populations from several regions of the world. In addition, AFB-Lys adduct has been used as a biological response indicator of acute and chronic human diseases, such as aflatoxicosis in Africa, risks of HCC in Taiwan, China and Africa, and infectious disease-linked immune suppression (Wang et al 1996(Wang et al , 1998Wang, Huang, et al 2001;Turner et al 2003;Azziz-Baumgartner et al 2005;Lewis et al 2005). Moreover, the AFB-Lys adduct has been used as the primary biomarker to assess the efficacy of several human chemoprevention and intervention trials ;W i l d&H a l l2000; Wang, Abubaker, et al 2001;W angetal.2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly significant associations between AFB-Lys adduct level and dietary AFB 1 exposure have been found in human populations from several regions of the world. In addition, AFB-Lys adduct has been used as a biological response indicator of acute and chronic human diseases, such as aflatoxicosis in Africa, risks of HCC in Taiwan, China and Africa, and infectious disease-linked immune suppression (Wang et al 1996(Wang et al , 1998Wang, Huang, et al 2001;Turner et al 2003;Azziz-Baumgartner et al 2005;Lewis et al 2005). Moreover, the AFB-Lys adduct has been used as the primary biomarker to assess the efficacy of several human chemoprevention and intervention trials ;W i l d&H a l l2000; Wang, Abubaker, et al 2001;W angetal.2008).…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin B 1 (AFB 1 ) is a potent hepatotoxic and genotoxic agent (Essigmann et al 1977;Wang & Groopman 1999), and has been evaluated as a Group I human carcinogen (sufficient evidence of carcinogenicity to humans) by the IARC, WHO (IARC 1993(IARC , 2002. Exposure to high levels of AFB 1 via the diet causes acute hepatotoxicity (aflatoxicosis) and death in humans, as demonstrated by recent outbreaks in Kenya, which were responsible for the deaths of more than 150 people (Azziz-Baumgartner et al 2005;Lewis et al 2005). Chronic exposure to low levels of AFB 1 is a risk factor in the aetiology of human hepatocellular carcinoma (HCC) in several regions of Africa and Southeast Asia, particularly in conjunction with hepatitis B virus infection (IARC 1993(IARC , 2002Wild & Hall 2000;Wogan et al 2012).…”
Section: Please Scroll Down For Arti Clementioning
confidence: 99%
“…It is estimated that 4.5 billion people are chronically exposed to aflatoxins in the developing world [4]. Periodic outbreaks of aflatoxicosis occur due to ingestion of contaminated food and result in hundreds of human deaths in Asia and Africa [5,6]. Furthermore, 58% of liver biopsies in cases of hepatocellular carcinoma have shown presence of aflatoxin B 1 (AfB 1 ) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The poor storage of agricultural produce can also lead to accelerated aflatoxin contamination as a result of proliferation of aflatoxin‐producing fungi. This has been demonstrated by many authors (Azziz‐Baumgartner et al., 2005; Mwalwayo & Thole, 2016). Some socioeconomic factors may also contribute to aflatoxins contamination, including informal marketing systems, inadequate transportation modes, unavailability of needed materials, tools, and equipment, lack of information and knowledge on appropriate pre‐ and postharvest managements, and poor governmental regulations and legislations.…”
Section: Resultsmentioning
confidence: 99%
“…In another severe aflatoxicosis outbreak, Azziz‐Baumgartner et al. (2005) also reported that aflatoxin contamination was found to be the cause of over 125 deaths during 2004–2005 in Eastern province of Kenya. Williams et al.…”
Section: Introductionmentioning
confidence: 96%